Darba tiesisko attiecību regulējums darbiniekiem Latvijas bankās - Ritums, Aldis (Latvijas Universitāte, 2009)
Kādas ir darba tiesisko attiecību regulējuma īpatnības Latvijas bankās? Autors darbā apskatījis likumdošanā noteiktās prasības un ierobežojumus atsevišķām bankas darbinieku kategorijām. Analizētas likumdošanas prasības attiecībā uz iekšējiem normatīviem aktiem, to specifiku bankās. Apskatīti iespējamie problēmjautājumi banku darbinieku darba tiesiskajās attiecībās. Sniegti priekšlikumi konstatēto pretrunu vai nenoregulēto jautājumu risināšanai.

Study- the labour legislation concerning employees of banking system in Republic of Latvia- the special requirements, limitations and restrictions as well as responsibility of employees. Aim of study- to find out in theoretical study of legislation and jurisprudence the problems that may arise for people who are working for banks; analysis of local legislative acts made by employer according requirements of national laws. The author had looked closely the legal provisions of labour legislation that are describing the necessity of working regulations in labour code. A comparison was made between terms and conditions of labour contract and working regulations. A special attention was spent to the Code of Conduct, establishment of which is defined by legislative acts of supervising institution- Financial and Capital Market Committee. A possible criminal offence and actions of employees of banks which may lead to criminal offence were analyzed. Summarizing, the author emphasizes the mostly significant cognitions, comes to conclusions and gives recommendations.
The Labour Legislation Concerning Employees of Banking System
Keywords: Juridiskā zinātne